ANALISIS YURIDIS PENGAJUAN GUGATAN PEMBATALAN PERJANJIAN PENGIKATAN JUAL BELI (PPJB) HAK ATAS TANAH OLEH PIIHAK CALON PENJUAL KARENA ADANYA GUGATAN DARI PIHAK KETIGA (STUDI PUTUSAN MA NO. 3703.K/PDT/2016) - FRANCO SENTANU (PREMISE LAW JURNAL, 2019)
Dosen Pembimbing:1. Prof. Dr. Budiman Ginting, SH, MHum2. Dr. T. Keizerina Devi A, SH, CN, MHum3. Notaris Dr. Henry Sinaga, SH, MKn Case of unilateral cancellation of PPJB on Land Rights in the Supreme Court's Ruling No. 3703.K / PDT / 2016 is done by returning the down payment that has been deposited to the Jayapura District Court but the defendant does not want to receive the deposited money because it does not want to cancel the PPJB and because of that the plaintiff filed a lawsuit against the defendant, the prospective buyer because he did not the existence of good faith. The research used normative judicial method which used a library research. The main stressing on this research is the legal standing of PPJB that is made by notary, the regulation of the cancellation of contract agreement and doing a juridical analysis on the supreme court’s ruling No. 3703.K/PDT/2016. The making of the PPJB should be accompanied by sanctions clauses regarding defaults in the implementation of the PPJB and the Notary is expected to be the mediator between the disputed prospective seller and buyer.